SIKAP PETANI TERHADAP PROGRAM TAMAN TEKNOLOGI PERTANIAN (TTP) BANTURUNG GARING HANTAMPUNG DI KELURAHAN BANTURUNG KECAMATAN BUKIT BATU - Marintan Naibaho; Eka Nor Taufik; Betrixia Barbara (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
The purpose of this research is to study the attitudes of farmers to the program of agricultural technology park (TTP) and to know the problems experience by farmers in Banturung Village, Bukit Batu Subdistrict. The method used in data collection in this study is by using the interview method with the help of questionnaires. This research was conducted in Banturung Village, Bukit Batu subdistrict. The results of this study indicate the attitude of farmers towards the TTP program is included in doubt category. This attitude is influenced by three components of attitude which are divided into nine variable indicators that is:The attitude of farmers towards technology which is classified as "agreed" includes: cognitive attitudes and affective attitudes, and those which classified as "doubtful" is conative attitudes. Then the attitude of farmers to training, which is classified as "agree" is; cognitive attitude, affective attitude and conative attitude. While the attitude of farmers to partnerships classified as "doubtful" is; cognitive attitude, affective attitude and conative attitude.The problem faced by farmers in the Banturung Garing Hantampung Agricultural Technology (TTP) program in Banturung Village, Bukit Batu Subdistrict is the lack of variation in technology implemented or produced through programs, agricultural machinery that is difficult to borrow and rental prices too high, training rarely held and less information from the group leader in informing the training schedule, the marketing of postharvest processed products is constrained due to the lack of partnership in the field of agribusiness and finance.